2007
DOI: 10.1007/1-4020-5579-x
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Learning – Signs, Discourses, Practices

Abstract: Aims & Scope "Lifelong Learning" has become a central theme in education and community development. Both international and national agencies, governments and educational institutions have adopted the idea of lifelong learning as their major theme for address and attention over the next ten years. They realize that it is only by getting people committed to the idea of education both life-wide and lifelong that the goals of economic advancement, social emancipation and personal growth will be attained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 0 publications
0
41
0
3
Order By: Relevance
“…She found that she read the book while on the exercise bike in the gym, on the tram to and from her office, in a doctor's waiting room, and on the bench in the park watching her son play. Usher and Edwards (2007) would probably describe this as a 'deterritorialised' learning practice, in that it involves a loosening up of traditionally conceived spaces for or of learning. She realised she had developed a habit of 'living with the text', and initially thought of this as an attempt to become more efficient.…”
Section: Inger's Story: 'The Day All My Network Broke'mentioning
confidence: 98%
See 2 more Smart Citations
“…She found that she read the book while on the exercise bike in the gym, on the tram to and from her office, in a doctor's waiting room, and on the bench in the park watching her son play. Usher and Edwards (2007) would probably describe this as a 'deterritorialised' learning practice, in that it involves a loosening up of traditionally conceived spaces for or of learning. She realised she had developed a habit of 'living with the text', and initially thought of this as an attempt to become more efficient.…”
Section: Inger's Story: 'The Day All My Network Broke'mentioning
confidence: 98%
“…One of the aims of the actor-network theory researcher is to avoid privileging the human as sole actor in his or her accounts, and thereby demoting the physical, material world to a subservient or purely instrumental role. Following this, and borrowing from Usher and Edwards (2007), a doctoral candidate can be understood as a 'knowing location' in a doctoral actor-network that consists of both human and non-human actors. Populating the rest of the network are relations with other knowers, such as the supervisor, peers and colleagues, and knowledge artefacts, such as journal articles, books and databases.…”
Section: Doctoral Candidature As Actor-networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, how adults establish, refine and strengthen subjectivities is of course also crucial in nuanced discussions on learning. If everyday life is considered to be a learning context in itself, there seems to be no doubt that powerful pedagogical forces are always present (Edwards, 2009;Giroux, 2004;Sandlin et al, 2010;Usher & Edwards, 2007). Who we are, who we are expected to be and who we will become is constantly negotiated, adjusted to and contested in the myriad of personal, private and public spheres where we live our lives.…”
Section: Stance Takings Styles and Adult Learningmentioning
confidence: 96%
“…The lifelong learning discourse promulgates a switch from a didactic, 'schooling' tradition of teaching to a more constructivist, 'developmental' approach (Usher and Edwards 2007) that requires an alteration in teachers' conceptualisation of their role and practice. A change in professional identity that entails teachers enabling pupils to build and create knowledge for themselves (Drew and Mackie 2011) rather than transmitting knowledge for them to absorb.…”
Section: Introductionmentioning
confidence: 99%